Pengembangan Keamanan Data Penerimaan Siswa Baru Berbasis Website - Nistia Laia; Muhammad Zen; Leni Marlina (CV. Hawari, 2026)
The process of new student admission involves the collection and management of sensitive personal data, which requires strong data security to prevent misuse and unauthorized access. SMP Swasta Pencawan Medan faces challenges in ensuring the confidentiality and integrity of prospective student data in its web-based admission system. This study aims to develop a secure web-based new student admission system by implementing data security mechanisms to protect against common web attacks such as SQL Injection, Cross-Site Scripting (XSS), and Cross-Site Request Forgery (CSRF). The research method used is system development, which includes system analysis, design, implementation, and testing. The system is developed using PHP as the programming language and MySQL as the database, with the application of the SHA-1 algorithm to secure sensitive data such as passwords. The results show that the developed system is capable of improving data security, maintaining data integrity, and preventing unauthorized access. The implementation of security mechanisms in the system contributes to a safer and more reliable new student admission process, thereby increasing trust from parents and the community.